The genus Encyclia Hook. (Orchidaceae, Epidendroideae) in Maranhão state, Brazil: new morphological data and extent of distribution - F. Ribeiro, Jaireslane (2026)
In this study, we report the diversity, geographical distribution, and ecology of the Encyclia species from the state of Maranhão, Brazil. For each species treated, we present morphological descriptions, geographic distribution maps, taxonomic and ecological comments, an identification key for the species occurring in the state and photographic plates. Three species were recorded: E. gonzalezii, E. granitica, and E. linearifolioides, with E. gonzalezii being endemic to Brazil. Encyclia granitica has been locally rediscovered approximately 93 years after its only known collection in Maranhão. We also included new morphological data for this species, for which a description of the fruits had not been available until now. We found that the epicarp of the three species exhibited significant morphological differences, which may aid in their identification and delimitation. Given the complicated taxonomy of the genus, further studies focused on the epicarp may determine the extent to which it can assist in distinguishing additional species and in assessing its phylogenetic signal.